An optimal allocation of asylum seekers - Oded Stark; Grzegorz Kosiorowski (University of Bonn, Center for Development Research (ZEF), 2024)
We formulate a rule for allocating asylum seekers that is based on the social preferences of the native workers of the receiving countries. To derive the rule, we construct for each country a social welfare function, SWF, where the social welfare of a population is determined both by the population's aggregate absolute income and by the population's aggregate relative income. In a utilitarian manner, we combine the social welfare functions of the countries into a global social welfare function, GSWF. We look for the allocation that yields the highest value of the GSWF. We draw on assumptions that pertain to the manner in which the asylum seekers join the income distribution of the native workers: we consider a case in which the arrival of the asylum seekers has only a minor effect on the absolute income of the native population, and in which following their admission and integration, the asylum seekers join the income distribution of the native population "from below," namely the incomes of the asylum seekers are lower than the incomes of the low-income native workers. The arrival of asylum seekers can, however, measurably affect the relative incomes of the native population. Our rule states that the share of asylum seekers to be optimally assigned to each country depends only on the aggregate of the income excesses experienced by the native populations in the receiving countries.
Keywords: C54; D62; D78; E61; E65; F22; F62; F68; I31; I38; J15; J48; J68; O15; 330; Asylum seekers; Policy formation; Relative deprivation; Global social welfare; Rule of allocation